The Characteristics of Emotional Response of Post-traumatic Stress Disorder and Post-traumatic Growth among Chinese Adults Exposed to an Explosion Incident - Wei, Chuguang; Han, Jin; Zhang, Yuqing; Hannak, Walter; Liu, Zhengkui (Frontiers in Public Health, 2017)
The present study evaluated the relationship between post-traumatic stress disorder (PTSD)and post-traumatic growth (PTG). A sample of 2,395 participants completed measures of posttraumatic stress disorder according to the Checklist-Civilian Version (PCL-C), Posttraumatic Growth Inventory (PTGI) and a trauma-exposure related survey. The results indicated that whereas PTSD was not correlated with PTG. It was positively correlated with the traumatic exposure level, but PTG was not observed in this phenomenon. Finally, we randomly selected 90 participants and divided them into groups of PTSD, PTG and control to compare their characteristics of emotional response through the affective priming paradigm. The data showed that PTSD required more time to do the priming task and PTG demonstrated no difference compared to the control group. Combined with previous research findings, the relationship between PTSD and PTG may depend on the type and severity of the trauma, the exposure level and other such parameters. In terms of positive outcome of trauma PTG displayed no changes of emotional performance from the perspective of behavior. The preliminary results suggested that PTG was more related to a self-reported or self-experienced state.